Politicization of Religion and Religionization of Politics in Islam: The Madkhaliyah and Surūriyah Narratives as Case-Studies - Ahmad Arikewuyo, Nafiu (Jurnal Usuluddin, 2022)
The interplay between religion and politics is of particular interest to sociologists and historians. On many accounts, the state has often used religion as a sacred weapon to promote its political legitimacy while religion on the other hand has used the reigning power to impose its doctrine on the masses. This manifestation has featured in the historical development of Muslim scholarship and political ascendancy respectively. Against this backdrop, this study examines the aforementioned feature in the contemporary Muslim narratives using the Madkhaliyah and Surūriyah trends as case studies. The study adopts historical and analytical methods of research. It reveals that the rise of the Surūriyah trend in Saudi constitutes a formidable threat to the political interests of the ruling dynasty; hence, the resort to its persecution by the state authorities. The theology of the Madkhaliyah group is opposed to political reformation, opposition, and awareness and it promotes a peaceful society under an unchecked tyrannical system.